A132 SMOOTH MUSCLE BIOPSIES FROM POEM PROCEDURES FOR ACHALASIA SHOW LACK OF FUNCTIONAL INNERVATION. (26th February 2020) - Rodrigues, D; Lourenssen, S; Bechara, R; Blennerhassett, M G
Abstract: Background: Idiopathic achalasia is a disease of the esophagus causing impaired peristalsis and absent lower esophageal sphincter relaxation. The etiopathogenesis of the disease is unclear but most histopathologic studies from surgical resections show an absence of nitric oxide-producing neurons in the myenteric plexus. The peroral endoscopic myotomy (POEM) procedure has evolved in the last decade to treat achalasia and has provided a unique way to sample diseased tissue from an otherwise inaccessible tissue compartment. Aims: To study the effects of achalasia on innervation of smooth muscle and smooth muscle phenotype. Methods: Patients with a diagnosis of achalasia based on high resolution manometry undergoing a POEM at Kingston general hospital were approached for enrollment between June 2017 to September 2018. Demographic information including age, symptom duration, previous treatments, and Eckhardt score was collected. Intraoperatively, biopsies of the circular smooth muscle (CSM) layer were taken at the proximal and distal extents of the myotomy and placed in formalin. Tissue was embedded in wax, sectioned and stained using immunocytochemistry (ICC) for neuronal, axonal and smooth muscle cell markers. This was compared to control tissue from patients undergoing gastroesophagectomy for adjacent malignancy. Results: Control tissue from 3 separate esophagectomies were obtained. Samples were obtained from a total of 25 patients (13 males), with a median age of 50 (IQR 38–67). Most patients had Type 2 achalasia (19 [76%]) followed by Type 1 and 3 (2, [8%] respectively). Two cases had conflicting manometric findings. The median duration of symptoms was 3 years (IQR 1.5–10.5) and the median Eckhardt score was 6.5 (IQR 5–9). In sample tissues, no neuronal cell bodies were detected in the CSM layer. ICC for the axonal marker PGP9.5 showed that CSM of achalasia samples were almost completely devoid of axon structure, independent of the subtype of achalasia, compared to abundant axon presence in control tissues. In parallel, ICC showed that cholinergic (ChAT) or nitrergic (nNOS) axonal subtypes were absent in biopsy CSM while abundant in controls. CSM cells displayed hypertrophy with no detection of proliferation by ICC (KI67) or alterations in the phenotypic marker SM-22. Conclusions: Preliminary results from advanced immunohistochemical techniques show the absence of functional innervation of the CSM layer of all patients with achalasia. This is characterized by a depleted excitatory and inhibitory axon population. Further studies are focused on defining differences in smooth muscle phenotype and the presence or absence of inflammatory cells within the CSM. Funding Agencies: None